Differenzierung Und Entwicklung / Differentiation and Development 1965
DOI: 10.1007/978-3-642-50088-6_37
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of tuberization in plants. (Tubers and tuberous roots.)

Abstract: The stem and root of certain plant species often become modified into structures whose form and function differ considerably from that of the typical organ. Moreover, though the functions of these two organs, when in their typical form, differ considerably among themselves, they assume upon modification a new, identical and most important one, that of food storage. Many of the plants with such modified stems or roots, e.g., the potato and the sugar beet, have become important food and feed crops and are good e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…The mechanism of tuberization has been the subject of considerable investigation in the past several decades. Environmental factors such as photoperiod, temperature, and nitrogen nutrition have a significant influence in controlling tuber formation and development (5). Nevertheless, the fundamental mechanisms for inducing the biochemical events leading to tuberization and controlling photosynthate partitioning in whole plants are important biological questions that remain unanswered.…”
mentioning
confidence: 99%
“…The mechanism of tuberization has been the subject of considerable investigation in the past several decades. Environmental factors such as photoperiod, temperature, and nitrogen nutrition have a significant influence in controlling tuber formation and development (5). Nevertheless, the fundamental mechanisms for inducing the biochemical events leading to tuberization and controlling photosynthate partitioning in whole plants are important biological questions that remain unanswered.…”
mentioning
confidence: 99%
“…(McCelland, 1928 ;Werner, 1942 ;Driver, 1943 ;Chapman, 1958 ;Gregory, 1965 ;Mendoza and Haynes, 1976 ;Ewing, 1978 ;Ewing and Wareing, 1978 ;Batutis and Ewing, 1982 ;Struik, van Huesden and Burger-Meijer, 1988 ;Wheeler, Tibbitts and Fitzpatrick, 1991). For the most part, these studies have shown that short days (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the expression of these genes in developing tubers, we used elevated sucrose concentrations to mimic physiological conditions. Sucrose is the major transport sugar in potato plants, and tuberization has been linked to the availability of photosynthates from leaves (6). Starch stored in tubers is dependent upon sucrose from the leaves as its biosynthetic precursor.…”
Section: Discussionmentioning
confidence: 99%